Influence of cattle grazing on the density of oak seedlings and saplings in a Tabor oak forest in Israel - Dufour-Dror, Jean-Marc (Acta Oecologica, 2007)
The effects of cattle grazing on the density of seedlings and saplings in a Tabor oak forest (Quercus ithaburensis subsp. ithaburensis) are investigated. The Tabor oak forest studied is located in a Nature Reserve in the Mediterranean region of Israel. Cattle graze at a stocking density of 0.71 head/ha for 6 months a year. The cattle grazing in the Nature Reserve is a beneficial management measure because it enhances plant species richness and reduces shrub encroachment. The impact of grazing on the densities of seedlings and young saplings was quantified in 46 large sampling plots (333 m2 each) distributed over two experimental sites; the first being used as a rangeland for decades while the second is a forest patch totally free from grazing. The density and the height of Tabor oak individuals in each sampling plot were recorded. Four height categories were distinguished with a special focus on young seedlings (<0.15 m), established seedlings and young saplings (0.15 m–1 m). The density of seedlings and young sapling in the grazed Tabor oak forest were, respectively, 61% to 67% lower than in the ungrazed treatment. Implications on the continuity of the entire Tabor oak forest ecosystem are discussed. Three management measures that enable to prevent a decrease in young oak densities are proposed – reduction of stocking rate, deferment of the commencement of grazing, and fencing young seedlings.
Keywords: Eastern Mediterranean; Israel; Management measures; Mediterranean deciduous oak forest; quercus ithaburensis subsp ithaburensis

Influence of cattle grazing on the density of oak seedlings and saplings in a Tabor oak forest in Israel - Dufour-Dror, Jean-Marc (Acta Oecologica, 2007)
The effects of cattle grazing on the density of seedlings and saplings in a Tabor oak forest (Quercus ithaburensis subsp. ithaburensis) are investigated. The Tabor oak forest studied is located in a Nature Reserve in the Mediterranean region of Israel. Cattle graze at a stocking density of 0.71 head/ha for 6 months a year. The cattle grazing in the Nature Reserve is a beneficial management measure because it enhances plant species richness and reduces shrub encroachment. The impact of grazing on the densities of seedlings and young saplings was quantified in 46 large sampling plots (333 m2 each) distributed over two experimental sites; the first being used as a rangeland for decades while the second is a forest patch totally free from grazing. The density and the height of Tabor oak individuals in each sampling plot were recorded. Four height categories were distinguished with a special focus on young seedlings (<0.15 m), established seedlings and young saplings (0.15 m–1 m). The density of seedlings and young sapling in the grazed Tabor oak forest were, respectively, 61% to 67% lower than in the ungrazed treatment. Implications on the continuity of the entire Tabor oak forest ecosystem are discussed. Three management measures that enable to prevent a decrease in young oak densities are proposed – reduction of stocking rate, deferment of the commencement of grazing, and fencing young seedlings.
Keywords: Eastern Mediterranean; Israel; Management measures; Mediterranean deciduous oak forest; quercus ithaburensis subsp ithaburensis